Analisis Pendapatan Petani Sayur di Kecamatan Wasile Kabupaten Halmahera Timur - Aswir Hadi; Ahmad Yani Abdurrahman (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2024)
Revenue is all receipts, whether cash or non-cash which are the proceeds and sales of goods or services within a certain period of time. Where the form of income formulation is π = TR-TC. In this study using a qualitative type of field research while the data analysis technique used is R/C ratio analysis (Return Cost Ratio) While the data collection method used is the data collection method by observation, interview (nterview) and documentation directly to Mekarsari Village, Wasile District, East Halmahera Regency. The purpose of this study is to find out what are the factors that affect the income of vegetable farming, To find out how big the income level of vegetable farming and to find out whether there is a difference in income for owner farmers and rental farmers in Mekarsari Village, Wasile District, Kabupeten, East Halmahera. As for the results obtained in this study: the first factor that affects the income of vegetable farming in Mekarsari Village, Wasile District, East Halmahera Regency is production costs, labor and land area. The income of vegetable farmers is Rp 237,000 to Rp 35,495,000 and the difference between the income of the owner and rental farmer in Mekarsari Village, Wasile District, Kabupeten, East Halmahera is very different. Because, the owner farmers own their own land so there is no need to incur additional costs to rent land, while for rental farmers they have to pay land rent which results in production costs increasing income is small. Vegetable farming in terms of the R/C ratio in Mekarsari Village, Wasile District, Kabupeten, East Halmahera can benefit farmers. This is shown by the results of the comparison between revenue and cost (R/C ratio). In addition, farmers need to increase the area of land multiplied, maintain the quality of vegetables harvested in order to increase vegetable farming income.